Empowering Students in the English Language Classroom: Strategies for Teacher Trainees - López Gándara, Yiyi (2018)
Taking Critical Language Awareness as a frame of reference, this article presents an experience carried out with a group of teacher trainees in the final year of the BA in Primary Education (English) at the University of Seville. The aim of the experience is to provide them with effective strategies to empower students in the English language classroom. The experience is comprised of a diagnostic test, a tailored seminar and a workshop, and it shows that a critical component must be included in teacher training programmes in order to ensure that English language learning contributes to learner empowerment.